Traditional Chinese medicine for functional gastrointestinal disorders and inflammatory bowel disease: narrative review of the evidence and potential mechanisms involving the brain-gut axis - Liu, RuiXuan; Luo, YunTian; Ma, JinYing; Zhang, Qi; Sheng, Yudong; Li, Jiashan; Li, Hongjiao; Zhao, TianYi (Frontiers in Pharmacology, 2024)
Functional gastrointestinal disorders (FGIDs) and inflammatory bowel disease (IBD) are common clinical disorders characterized by recurrent diarrhea and abdominal pain. Although their pathogenesis has not been fully clarified, disruptions in intestinal motility and immune function are widely accepted as contributing factors to both conditions, and the brain–gut axis plays a key role in these processes. Traditional Chinese Medicine (TCM) employs a holistic approach to treatment, considers spleen and stomach impairments and liver abnormality the main pathogenesis of these two diseases, and offers a unique therapeutic strategy that targets these interconnected pathways. Clinical evidence shows the great potential of TCM in treating FGIDs and IBD . This study presents a systematic description of the pathological mechanisms of FGIDs and IBD in the context of the brain–gut axis, discusses clinical and preclinical studies on TCM and acupuncture for the treatment of these diseases, and summarizes TCM targets and pathways for the treatment of FGIDs and IBD, integrating ancient wisdom with contemporary biomedical insights. The alleviating effects of TCM on FGID and IBD symptoms are mainly mediated through the modulation of intestinal immunity and inflammation, sensory transmission, neuroendocrine–immune network, and microbiota and their metabolism through brain–gut axis mechanisms. TCM may be a promising treatment option in controlling FGIDs and IBD; however, further high-quality research is required. This review provides a reference for an in-depth exploration of the interventional effects and mechanisms of TCM in FGIDs and IBD, underscoring TCM’s potential to recalibrate the dysregulated brain–gut axis in FGIDs and IBD.